2020
DOI: 10.3389/fpsyg.2019.02915
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movements in Real-World Scene Photographs: General Characteristics and Effects of Viewing Task

Abstract: The present study examines eye movement behavior in real-world scenes with a large (N = 100) sample. We report baseline measures of eye movement behavior in our sample, including mean fixation duration, saccade amplitude, and initial saccade latency. We also characterize how eye movement behaviors change over the course of a 12 s trial. These baseline measures will be of use to future work studying eye movement behavior in scenes in a variety of literatures. We also examine effects of viewing task on when and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 97 publications
2
21
0
Order By: Relevance
“…Data analysis was based on 52,246 fixations across participants and scenes, with a mean of 33 fixations per scene (SD = 6.98 fixations), a mean fixation duration of 318 msec (SD = 69 msec), and a mean saccade amplitude of 2.84°( SD = 0.66°). Eye-movement measures were comparable to those typically obtained for similar scenes viewed outside the scanner (Cronin, Hall, Goold, Hayes, & Henderson, 2020;Castelhano, Mack, & Henderson, 2009).…”
Section: Eye-movement Analysissupporting
confidence: 70%
“…Data analysis was based on 52,246 fixations across participants and scenes, with a mean of 33 fixations per scene (SD = 6.98 fixations), a mean fixation duration of 318 msec (SD = 69 msec), and a mean saccade amplitude of 2.84°( SD = 0.66°). Eye-movement measures were comparable to those typically obtained for similar scenes viewed outside the scanner (Cronin, Hall, Goold, Hayes, & Henderson, 2020;Castelhano, Mack, & Henderson, 2009).…”
Section: Eye-movement Analysissupporting
confidence: 70%
“…One detail immediately worth noting is that saccade amplitudes increase, plateau, and then decrease, so a more accurate approach may be to use the less-eloquent term "fine-to-coarse-to-fine" behavior. A relationship between ordinal fixation number and both fixation durations and saccade amplitudes has also been reported in the scene perception literature (Castelhano et al, 2009;Cronin et al, 2020), suggesting that this behavior is not limited to simple visual search displays alone.…”
Section: Pitfall #2: Failing To Consider Coarse-to-fine Behavior Whensupporting
confidence: 53%
“…In previous studies, evidence for object-based selection in scenes was found for different task instructions 5,19 . In addition, studies in which a scene memorisation task was compared with an aesthetic preference judgement task have revealed only subtle differences in eye-movement behaviour 64,[69][70][71] . Nevertheless, we cannot exclude the possibility that our object-related memory questions have biased participants toward fixating individual objects in the scenes.…”
Section: Discussionmentioning
confidence: 99%